Estructura de conocimiento práctico del docente de la facultad de psicología de la Universidad Católica de Colombia y los procesos educativos que se desarrollan en el aula de clase : aproximación al problema. (1999)
The objective of this investigation was to comprehensively describe, characterize and analyze the relationship between the practical knowledge and the pedagogical practice of the professors at the Faculty of Psychology at the Universidad Católica de Colombia. The Hermeneutic Circle as a perspective of interpretative research was used. The sample group consisted of ten undergraduate and postgraduate teachers, both male and female, 24 to 44 years of age who were connected to the Psychology Faculty as full-time or part time professors for a period ranging from one to ten years. To collect data, participatory observation, semi-structured survey and the documentary files of the Curricular Planning and Evaluation Unit at the Faculty of Psychology, were used as instruments.The obtained data were grouped into the following categories: planning, decision making, interactive thoughts and theories and beliefs. The principles identified in the contents of professors?practical thinking are . sharing power, progressive verification, suppression of emotion, practical principles, rule of the practice, images, and imperative knowledge. In the sample group the application of the principle of compensation was not found and in some of the cases, the principle of closing was found. The knowledge structures showed by the professors studied correspond to a set of concepts and theories which are a product of their formative process in the field of Psychology as well as the subjects they deal with.